A estética melancólia do fim e a atuação extra-fílmica em Lars Von Trier - Andrade, Manuela Bezerra Gouveia de (2015)
The research brings some previous movies of the Danish filmmaker that keep a relation with the aesthetic atmosphere and extra-filmic performance embraced, and, through an approach about the stylistic, mythical and performatic language, makes a poetic essay on the theme. The present study establishes reflections on the technical resources (photography, color temperatures, edition) as well as about the mise en scène that the filmmaker uses to narrate such apocalyptic plot. This imagery speech was an instrument to work with issues related to finitude, the cosmogony, the melancholy and the imaginary. The dissertation also analyzes the performative role of the author and how this content can influence the viewer’s fruition, it also considerates how this process - before the press - functions as a crucial element of insertion of Danish cinema in the international market, specifically the production company founded by Trier and Peter Aalbeak, the Zentropa.The main theoretical support to deal with authorship, extra film and contemporary melancholy are: Michel Foucault, Mikhail Bahktin and Maria Rita Kehl and to understand the archetypes and the filmic aesthetics in the narrative: Carl Jung, Gilbert Durand, David Bordwell, Jack Stevenson Giorgio Agamben and Arthur Schopenhauer.